Advances in plant materials, food by-products, and algae conversion into biofuels: use of environmentally friendly technologies. Issue 12 (9th May 2019) - Kamani, Mohammad Hassan; Eş, Ismail; Lorenzo, Jose M.; Remize, Fabienne; Roselló-Soto, Elena; Barba, Francisco J.; Clark, James; Mousavi Khaneghah, Amin
Abstract : Green technologies have emerged as useful tools for the generation of clean fuels with the potential to minimize the effect of human activity on the environment. Abstract : Green technologies have emerged as useful tools for the generation of clean fuels with the potential to minimize the effect of human activity on the environment. Currently, these fuels are mainly composed of hydrocarbons obtained from crude oil. Over the past two decades, biomass has gained significant attention as a renewable feedstock for more sustainable biofuel production and has been a great candidate to replace fossil fuels. The principal components of most of the available biomass are cellulose, hemi-cellulose, and lignin. Although the available green technologies for biofuel production are progressing rapidly, productivity and chemical yield from these techniques are still below the required values. Therefore, there is a need for interdisciplinary studies to meet the requirements for more global and efficient production by streamlining processes, integrating technologies and achieving techno-economic improvements. In this context, we aim to give an overview of available biomass such as agricultural wastes suitable for the generation of different classes of biofuels including next-generation biofuels. Unfortunately, expensive, wasteful and energy-consuming pretreatment processes are still used. Therefore, novel technologies that allow a more efficient separation with low resource consumption and the generation of a low number of residues are required. In this regard, novel technologies such as efficient fractionation techniques and genetic and metabolic engineering including the application of CRISPR/Cas tools, as well as microfluidic platforms to improve the overall yield of biofuel production are discussed.